Analisis Peran Supervisi Kepala Sekolah terhadap Pelaksanaan Tugas Pokok Guru; Studi Tindakan Sekolah di SMPN 2 Situjuah Limo Nagari - Arnel Wandi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
The school supervision that carried out by the principal will have a significant impact of the implementation in the learning process by the teacher in the school. The implementation is also a manifestation of the effectiveness of learning programs in supporting the teacher's main tasks. However, preliminary studies in the field showed that in general the research subjects were still not optimal in carrying out their main tasks, such as the lack of a learning plan, less optimal use of learning media, evaluation not being compiled and the results of assessments not being used optimally. This study aims to provide the principal's supervision actions on the implementation of the teacher's main tasks through a series of treatments in two cycles. This research consists of 21 teachers at SMPN 2 Situjuah Limo Nagari, Lima Puluh Kota District. The results of the study have proven that the implementation of school principal’s supervision can improve the implementation of the main tasks.